The Effect of ND:YAG Laser Posterior Capsulotomy Size on Refraction, Intraocular Pressure, and Macular Thickness. (3rd March 2014) - Karahan, Eyyup; Tuncer, Ibrahim; Zengin, Mehmet Ozgur
Abstract : Purpose . The aim of this study is to examine the influence of capsulotomy size on, spherical equivalent (SE), intraocular pressure (IOP), and macular thickness. Materials and Methods . Sixty-eight patients were examined preoperatively and 1, 4, and 12 weeks after Nd:YAG capsulotomy. Patients were divided into two groups based on the postoperative capsulotomy size. Changes in SE, IOP, and macular thickness were compared between two groups. Results . We found a higher hyperopic shift in large capsulotomy group. In both groups 1 and 2, IOP increased 1 week postoperatively. Intraocular pressure rise in group 2 was higher than in group 1. Both groups had increased macular thickness at 1 week postoperatively. The degree of macular thickening was similar in group 1 and group 2. Comment . Patients who underwent a larger capsulotomy have a higher hyperopic shift and IOP elevation. Rise in macular thickness was similar in large and small capsulotomy groups.